Schumpeter and venture finance: radical theorist, broke investor, and enigmatic teacher. (15th March 2015) - Peneder, Michael; Resch, Andreas
Abstract : Schumpeter's relation to venture finance constitutes a fascinating, yet so far unacknowledged, chapter of his biography and financial history. Presenting new historical evidence and pointing out connections that have so far escaped attention, we first discuss Schumpeter's venture theory of money and banking, then his personal history as a broke investor in Vienna, and finally his influence on the emerging venture industry during his later years at Harvard. We show how the theoretical vision inspired his own failed effort as a venture investor in the 1920s, and provided a powerful intellectual frame for the later development of venture finance in the 1940s.